The role of traditional dance movements in balance and flexibility - Sahbana Ridha; Tri Yonisa; Arham Syahban; Putri Yunita Permata Kumala Sari (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: Much research on physical fitness remains focused on conventional sports, while the potential of traditional dance movements in enhancing balance and flexibility has been insufficiently investigated scientifically. In Indonesia, particularly South Kalimantan, traditional dances such as Baksa Kembang Dance and Radap Rahayu Dance possess movement characteristics that theoretically can train postural control and joint mobility, yet their physical fitness effects remain undocumented in the scientific literature. Purpose: This review aims to examine the contribution of traditional dance movements to balance and flexibility and to identify research gaps in South Kalimantan traditional dances. Methods: This study employed a narrative literature review design. Systematic searches were conducted across Scopus, Web of Science, and SINTA databases for publications from 2010–2025 using keywords related to traditional dance, balance, and flexibility. Articles meeting inclusion criteria were peer-reviewed publications in English or Indonesian that investigated the effects of traditional dance on physical fitness components. Data were extracted and synthesized thematically. Results: The review findings demonstrate that traditional dance training programs consistently improve static and dynamic balance, muscular flexibility, and joint mobility, particularly among elderly populations. Underlying mechanisms include neuromuscular adaptation, sensorimotor integration, and strengthening of supporting muscles. However, the literature search identified a complete absence of empirical studies specifically investigating South Kalimantan traditional dances. Most evidence derives from Greek, Thai, Chinese traditional dances, and Balinese Lègong dance. Some studies show inconsistent results regarding flexibility and body composition, possibly due to heterogeneity in intervention design and participant characteristics. Conclusion: Traditional dance movements possess significant potential as holistic and culturally sensitive physical fitness interventions, and can be integrated into physical education programs and community health promotion. However, rigorous empirical research is urgently needed to investigate the specific fitness effects of South Kalimantan traditional dances to strengthen the evidence base and facilitate scientifically grounded practical application.